Metode Yanbu’a dalam Penanaman Kemampuan Membaca Huruf Hijaiyah pada Santri TPQ At-Tauhid Tuban - Aya Mamlu'ah; Devy Eka Diantika (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2018)
Planting the ability to read Hijaiyah letters is a common thing for the Al-Qur'an Education Park. The main problem often faced by TPQ students in the Al-Qur'an Education Park in the Senori sub-district is the method used in the ability to read hijaiyah letters. The background of this writing is that the 3-year-old santri who followed the learning process of reciting in the TPQ At-Tauhid Leran Senori Tuban. This research is a qualitative classroom action research (PTK), taking location in At-Tauhid Leran TPQ Senori Tuban. Data collection is done by interviewing, observing and documenting, data analysis is done by giving meaning to the data that has been collected and from that meaning drawn conclusions. The results of the application of the Yanbu'am method show a significant increase in reading ability which initially 43% rose to 55% in cycle I and become 75% in Cycle II. Thus the method of yanbu'a can instill the ability to read hijaiyah letters in santri at TPQ At-Tauhid Leran Senori Tuban.